Reactive Power Analysis At Solar Power Plant - Abdul Kadir, Aida Fazliana; Mupangat, Hanisah; Rasin, Zulhani; Mat Said, Dalila (Penerbit UTM Press, 2021)
Reactive power is essential to control the power system's voltage stability as the reactive power is directly proportional to the voltage. Hence, every new solar photovoltaic (PV) plant installed in the grid system must comply with the grid code requirements to ensure that the electricity supply remains stable and reliable. As the more penetration of PV plants, the electrical system will face some challenges related to reactive power control and voltage support. Thus, many countries including Malaysia have updated their grid codes to permit a smooth interaction between these new plants with the grid system. The inverter of PV solar connected to grid system are required to supply rated power output (MW) at point of common coupling (PCC) between the limits of 0.85 power factor lagging, and 0.95 leading follow to the Malaysian Grid Code (MGC) requirement. Hence, this research aims to design a controller for the PV inverter in Matlab/Simulink that able to absorb and supply the reactive power. Then, the comparison will execute between the simulation results and the MGC requirement. However, due to power loss in the system, the PV inverter controller may not comply with the reactive power capability as the MGC requirement. Thus, the PV system need to integrate with the capacitor bank as a reactive power compensator.